Reclaiming Table Mountain: Perspectives from Cape Town's Black Township Residents - Mjenxane, Lindela (School of African and GenderStuds, Anth and Ling, 2023)
The aim of this study was to investigate how the landless township residents of Cape Town could reclaim the iconic Table Mountain, for it to be fully inclusive in a manner that is meaningful and useful in their traditional and cultural practices. This study explored the request made by traditional surgeons and traditional leaders to have a portion of an un-serviced land on Table Mountain rezoned for Ulwalukho (Male Circumcision). This study calls for the management of Table Mountain to recognise the rights of the township residents of Cape Town to participate in the policy decisions, conservation management and heritage strategies of Table Mountain in order to ensure its inclusive use. This qualitative study made use of ethnography, auto-ethnography and mobile methods. Individual in-depth interviews were also conducted, with the 10 purposely sampled youth and adults. This study found that Table Mountain could play a pivotal role in the transitional process of young people who interact with the ecological world, providing them a form of nature therapy that has improved their well-being. This study also found that it is feasible to have a piece of Table Mountain rezoned for Ulwaluko (Male Circumcision). This study further found that black township residents of Cape Town must be integrated into the conservation agenda, policy decisions and strategic decisions pertaining to the management of Table Mountain. The conservation of the Cape Floral Kingdom on Table Mountain should be pursued in ways that are not to the detriment of, or threatening to the cultural practices of black township residents of Cape Town. This mountain must fully be inclusive in its practical sense not merely in theory, but in a manner that also appeases local people of Cape Town.